From ultra-high molecular weight polydimethylsiloxane to super-soft elastomer. (November 2019) - Tugui, Codrin; Tiron, Vasile; Dascalu, Mihaela; Sacarescu, Liviu; Cazacu, Maria
Graphical abstract: Highlights: Ultra-high molecular weight polydimethylsiloxane of narrow polydispersity is obtained. Bulk anionic ring-opening polymerization with transient catalyst is a clean procedure. Individual or aggregated macromolecules are assessed by DLS, TEM and AFM. Soft elastomer is obtained by cross-linking the ends of ultra-long polysiloxane chains. The elastomer has high elastic recovery and low stress decay at high elongation. Abstract: A polydimethylsiloxane-α, ω-diol (UHMW-PDMS) with unusually high molecular weight (Mw = 1, 395, 000 g/mol) and narrow polydispersity (PDI = 1.49), free of monomer or catalyst traces, was obtained in high yield by a scalable process, easy to achieve (bulk anionic ring-opening polymerization of octamethylcyclotetrasiloxane catalyzed by tetramethylammonium hydroxide). Spectral and thermogravimetric analysis confirmed the theoretical structure, purity and thermal stability of the polymer. Individual or aggregated macromolecules were assessed by dynamic light scattering (DLS) and visualized by microscopic methods (TEM, AFM). The mechanical, dielectric, and thermal performances of application interest for this polymer were evaluated on samples of chemically defined elastomer cUHMW-PDMS prepared by condensation crosslinking through the polymer chain ends with tetraethylorthosilicate. The results were compared with those obtained on a lower molecular weight (Mw = 720, 100 g/mol, PDI = 1.87) homologue (PDMS) prepared and processed in identical conditions, but also with a commercial silicone elastomer. UHMW-PDMS-based elastomer shows superior results on elastic recovery and stress decay at high elongation, as compared with reference samples.